the Effects of Piper ribesioides on Growth Performance, Carcass traits and meat quality of Muscovy Duck - bounyavong, somphanh; VAENVONGTHONG, Davanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Effects of Piper ribesioides on Growth Performance, Carcass traits and meat quality of Muscovy Duck DavanhVAENVONGTHONG1*, Bounmy KEOHAVONG2, Somphanh BOUNYAVONG3 Animal Science Program, Faculty of Agriculture and Forest Resource, Souphanouvong University, Lao PDR 1Correspondence: Davanh VAENVONGTHONG, Lao-China Agriculture technical demonstration Development and Service Center, Oudomxai Province, Tel: +856 20 28296939, E-mail: Davanhvvt@gmail.com 2Correspondence: Office of Research and Academic Services, Souphanouvong University 3Correspondence: Department of Animal Science, Faculty of Agriculture and Forest Resource, Souphanouvong University Abstract The objective of this study was to compare the effects of Piper ribesioides (Pr) on the growth performance, carcass traits, and meat quality of Muscovy ducks. The study was conducted from July to October 2023 at the Faculty of Agriculture and Forest Resource, Souphanouvong University. Three levels of Pr were compared in this study: 0.25, 0.25, and 0.5%. The ducks were fed ad libitum and were weighted every seven days until the 70-day mark. After the feeding trial was completed, the duck was killed to compare the carcass. The study's findings were as follows: Feed intake, measured in grams per head per day and grams per kilogram LW, was found to be significant (P<0.05). Increasing the level of Pr also had an effect on growth performance and live weight, with live weight increasing throughout each period but not during period 1. Period 5 also showed a high level of effect from increasing the level of Pr, with average daily gain reaching its highest point at 0.5% = 52.47 g/day, 0.25% = 48.66 g/day, and the lowest point at 0% = 44.59 g/day. Additionally, the feed conversion ratio improved at 0.5% = 4.93, 0.25% = 4.94, and 0% = 5.10. Live weight prior to death was significant (P<0.05); however, organs and carcasses were not (P>0.05), only the liver and lung were. Duck meat water loss includes: Breast after boiling for 45 minutes, 24 hours, and freezing for 45 minutes was not significant (P>0.05), but freezing for 24 hours was significant (P<0.05). On the other hand, drumsticks boiling for 45 minutes, 24 hours, and freezing for 24 hours were not significant, but freezing for 45 minutes was significant. The duck breast and drumsticks color systems of L*, a*, and b* at 45 minutes and 24 hours were significant (P<0.05), and the drumsticks and breast pH were significant (P<0.05).